Menggait Generasi Milenial Melalui Penerapan Dakwah Kultural Dalam Media Sosial - Nur Halimatus; Abdul Muhid (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
The millennial generation is a generation that can be said to be very familiar with the technology that is developing at this time, of course in this case millennials are included in a special category, seeing from the habits that have coexisted with social media, it has become a culture when viewed from its characteristics, then da'wah cannot run just slack, it needs a special strategy to attract this generation, by using interpretive qualitative methods, the author tries to interact through context, and look for written sources, with the results of cultural da'wah is one of the effective strategies for the Islamization of the Earth, identification of da'wah objects through their characteristics encouraging preachers to flex their da'wah according to the medium while paying attention to the lines of da'wah, by using social media to post interesting content by paying attention to images, duration and also the choice of material, to be a powerful strategy, accompanied by informative and solid and clear points, use of light language are also a consideration, such as several preachers who are popular among millennials, Husein Basyaiban, Ustad Hanan Attaki and also Ning Umi Laila, for example.